2012
DOI: 10.1142/s0219525912500622
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Social Network in an Internet Political Discussion Forum

Abstract: We present an analysis of the properties of a social network, formed by users participating in one of the most popular Polish political discussion forums, during a period of two years. We find that despite communication motivated mostly by controversy and negative emotions, the resulting social network is remarkably similar to networks found in discussion boards based on similarity of views. All collected messages have been analyzed to determine their content type, author's political sympathies and emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Data from the case primarily suggests that while over time some discussion groups do feature some spurts of cross-opinion interactions, the overall process over time does not feature the key feature of public deliberation, that is interaction with participants of different opinions. With only one exception, all of the four discussion dynamics observed feature consistent evidence of homophily increasing over time, a finding in line with previous studies on sentiments and polarization in online social networks (Hillmann & Trier, 2012, 2013Sobkowicz & Sobkowicz, 2012a, 2012bY. Yang et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Data from the case primarily suggests that while over time some discussion groups do feature some spurts of cross-opinion interactions, the overall process over time does not feature the key feature of public deliberation, that is interaction with participants of different opinions. With only one exception, all of the four discussion dynamics observed feature consistent evidence of homophily increasing over time, a finding in line with previous studies on sentiments and polarization in online social networks (Hillmann & Trier, 2012, 2013Sobkowicz & Sobkowicz, 2012a, 2012bY. Yang et al, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Findings link the observed phenomenon of homophily to a fragmentation of the public into divided electronic communities made of groups that tend to self-segregate (Lawrence, Sides, & Farrell, 2010;Van Alstyne & Brynjolfsson, 2005). As a result, homogeneous groups tend to polarize, and thus radicalize their positive or negative sentiments (Sobkowicz & Sobkowicz, 2012a, 2012b.…”
Section: Previous Research: Online Public Deliberation and Network Homentioning
confidence: 84%
“…Part of the model legacy comes from extended studies of the behavior of the users of Internet fora related to the Polish politics between 2009 and 2011, where we have observed strong correlations between the expressed opinions and emotions of the participants [ 61 63 ]. In particular, we have observed that when the emotional arousal of the participants is high, their capacity to change opinions is negligibly small.…”
Section: General Model Descriptionmentioning
confidence: 99%
“…. The analysis of the political discussion fora confirms this reasoning [38,52,53]. Even in the situations where proponents of the opposing opinions actively seek out contact with each other, the chances of influencing the opinion of the opponents are practically zero.…”
Section: Discussionmentioning
confidence: 59%